Factors affecting uptake of cervical cancer screening among African women attending selected churches in the Klang Valley, Malaysia - Cecilia, Nwabichie Chinermerem (2018)
Introduction: Cervical cancer is a health concern among women worldwide as it ranks as the fourth most common type of cancer among women. Human papillomavirus (HPV) 16 and 18 are the main causative agent of Cervical cancer. Cervical cancer can, however, be prevented with early and regular cervical cancer screening. Appropriate and regular cervical cancer screening can reduce Cervical cancer incidence and mortality by as much as 80%. So many factors such as Insurance status, income, educational level, Knowledge, perceived barriers and many others have been determined by researchers to be significantly associated with the uptake of cervical cancer screening. Objective: This study aims to identify the cervical cancer screening practices and factors affecting the screening status of African immigrant women attending selected church services in Klang Valley, Malaysia. Methodology: A cross-sectional study among 320 randomly selected respondents between ages 18-69 was conducted in three different churches with high number of African participant in Klang Valley. A structured questionnaire was used to conduct a face to face interview. Three levels of analysis were conducted using SPSS 21, involving descriptive analysis, chi square and multiple logistic regression. Results: The response rate was 98.2%, majority of the respondents were aged 31-50 years, and married. The prevalence of screening among the respondents since the past 3years was 27.2%. Using a p-value of 0.05 as the significance level, the final model showed that marital status (p=0.004, AOR=2.257, 95%CI=1.006-4.361), knowledge (p=0.035, AOR=3.217, 95%CI= 1.027-6.216), perceived barriers (p=0.003, AOR=3.110, 95%CI=2.461-6.426) and having a regular health care provider (p<0.001, AOR=2.693, 95%CI=1.001-4.361) were the only significant predicting factors of uptake of cervical screening among African immigrant women in Klang Valley, Malaysia. Conclusion: The findings revealed that the uptake of cervical cancer screening among the respondents since the past 3years was very low. Marital status, Regular health care provider, knowledge and perceived barriers are the predicting factors. The government and ministries concerned with cervical cancer screening should develop and increase intervention programs and public health enlightenment messages through the mass media, hospitals, schools and so on, which will also reach this target group. There is also a need to educate the spouses about cervical cancer screening as spousal support could serve as a source of encouragement to the women to go for screening.